(untitled) (Research, Society and Development, 2021)
This study aimed to bring a discussion and analysis about home physiotherapeutic care to the elderly with diabetes mellitus through an integrative review in the electronic databases BVS and PubMed portal using the descriptors physiotherapy, elderly, diabetes mellitus and home treatment and search strategies, inclusion and exclusion criteria of findings published from 2016 to 2021. With the descriptors selected, 105 findings resulted and after reading in full thus totaling an eligibility of 17 articles. Physiotherapeutic home care for the elderly with diabetes involves several stages and care resources, from rehabilitative to preventive actions, with the elderly or with their environment and people, and is evidenced to be of great importance. This home care emerges as an effective alternative, and is capable of contributing to the healthier aging of the elderly in several aspects, promoting better quality of life and qualification of the professional physiotherapist, in relation to the preparation and attention to the basic human needs of the elderly, their caregivers and/or family members. It is noteworthy that the physiotherapeutic care at home for this elderly with diabetes provides a range of actions and adaptations to the extent that this care is performed where the elderly live and relate. We point out the need for another study on this theme that addresses more specificities of physical therapy with the caregiver and family of this elderly patient.